Molecular phylogenetic relationships of the Liolaemus rothi complex and a new species of lizard from Auca Mahuida Volcano (Squamata: Liolaemini) - Avila, Luciano Javier; Olave, Melisa; Perez, Cristian Hernan Fulvio; Perez, Daniel Roberto; Morando, Mariana (Zootaxa, 2013)
A new species of lizard of the genus Liolaemus from Neuquén Province, western Argentina, is described. The new species is a member of the Liolaemus rothi species complex, and mitochondrial and nuclear molecular data show it as sister taxon of the clade composed of (L. hermannunezi (L. tromen + L. loboi)), differing in size, squamation, coloration, and sexual dimorphism from the other species of this group. Liolaemus sitesi sp. nov. has a dark body coloration with series of notched blotches on the dorsum, with bright spots, and a very iridescent yellow-green coloration in natural light. Liolaemus sitesi sp. nov. is found only in the Auca Mahuida volcano and is terrestrial, dwelling on the stony slopes with sandy soil between 1300 m and the volcano summit.